Prostate Cancer Burden at the Uganda Cancer Institute - Okuku, Fred (J Glob Oncol, 2016)
PURPOSE: In Uganda, the incidence of prostate cancer is increasing at a rate of 5.2% annually. Data describing presentation and outcomes for patients with prostate cancer are lacking. METHODS: A retrospective review of medical records for men with histologically confirmed prostate cancer at the Uganda Cancer Institute (UCI) from January 1 to December 17, 2012, was performed. RESULTS: Our sample included 182 men whose mean age was 69.5 years (standard deviation, 9.0 years). Patients who presented to the UCI had lower urinary tract symptoms (73%; n = 131), bone pain (18%; n = 32), increased prostate-specific antigen (PSA; 3%; n = 5), and other symptoms (6%; n = 11). Median baseline PSA was 91.3 ng/mL (interquartile range, 19.5-311.3 ng/mL), and 51.1% of the patients (n = 92) had a PSA value above 100 ng/mL. Gleason score was 9 or 10 in 66.7% of the patients (n = 120). Ninety percent (n = 136) had stage IV disease, and metastatic sites included bone (73%; n = 102), viscera (21%; n = 29), and lymph nodes (4%; n = 5). Spinal cord compression occurred in 30.9% (n = 55), and 5.6% (n = 10) experienced a fracture. A total of 14.9% (n = 27) underwent prostatectomy, and 17.7% (n = 32) received radiotherapy. Gonadotropin-releasing hormone agonist was given to 45.3% (n = 82), 29.2% (n = 53) received diethylstilbestrol, and 26% (n = 47) underwent orchiectomy. Chemotherapy was administered to 21.6% (n = 39), and 52.5% (n = 95) received bisphosphonates. During the 12 months of study, 23.8% of the men (n = 43) died, and 54.4% (n = 98) were lost to follow-up. CONCLUSION: UCI patients commonly present with high PSA, aggressive Gleason scores, and stage IV disease. The primary treatments are hormonal manipulation and chemotherapy. Almost 25% of patients succumb within a year of presentation, and a large number of patients are lost to follow-up.